Predictive modeling of 3D reconstruction trajectories for potential programmable materials - Jin, Yechun; Li, Jie; Yu, Qi; Tian, Panghua (Frontiers in Materials, 2025)
IntroductionShape-morphing programmable materials, capable of dynamically adjusting their properties in response to external stimuli, hold significant potential in adaptive design and smart manufacturing. However, accurately predicting their 3D reconstruction trajectories remains a challenge due to the complex interactions between material behavior and environmental factors.MethodsTo address this, we propose a computational framework, the Dynamic Morphology Engine (DME), designed to enhance predictive modeling of shape-morphing programmable materials by integrating advanced control mechanisms and optimization strategies. The DME framework consists of three key components: Stimulus Mapping, Property Optimization, and Structural Adaptation, enabling efficient trajectory prediction in dynamic environments. Additionally, we introduce the Stimulus-Informed Design Paradigm (SIDP), which leverages data-driven modeling to refine the interplay between external stimuli and material responses.Results and discussionExperimental results demonstrate that our approach improves robustness, scalability, and computational efficiency, offering a promising tool for modeling shape-morphing programmable materials in applications such as soft robotics, reconfigurable structures, and intelligent materials.